Facilitators and barriers to optimizing eating performance among cognitively impaired older adults: A qualitative study of nursing assistants' perspectives. (27th November 2018) - Liu, Wen; Tripp-Reimer, Toni; Williams, Kristine; Shaw, Claire
Background and Objectives: Cognitively impaired individuals are at increased risk for functional and behavioral difficulties at mealtimes, leading to compromised eating performance, low food and fluid intake, and negative functional and nutritional outcomes. Nursing assistants are the most critical front-line care staff and best positioned to manage the personal and environmental factors that influence resident eating performance. Identifying nursing assistants' perceptions of barriers and facilitators to engaging residents in eating will provide important experientially based foundation for developing and testing evidence-driven interventions to promote mealtime care. Methods: A qualitative descriptive study was conducted in three sites: two nursing homes and one hospital gero-psychiatric inpatient unit. Six focus groups were conducted with a purposive sample of 23 nursing assistants who regularly provided mealtime care to residents with cognitive impairment. Interview questions addressed barriers and facilitators at resident, caregiver, environmental (facility), and policy levels in optimizing mealtime care. Audio recordings of focus groups were transcribed and analyzed using qualitative descriptive content analysis. Both barriers and facilitators were organized into a hierarchical taxonomy based on similarities and differences framed by the Social Ecological Model. Results: The majority of barriers and facilitators were at the caregiver level. Caregiver-level barriers included lack of preparation and training, competing work demands, time pressure, and frustration. Caregiver-level facilitators included caregiver preparation and motivational, technical, informational, and instrumental assistance. Environmental-level barriers and facilitators related to the physical, social, and cultural environment and facility practices. Only barriers to optimizing mealtime care were identified at resident and policy levels. Conclusions: Nursing assistants identified multilevel barriers as well as a wide range of caregiver and environmental facilitators to optimizing dementia mealtime care. Findings can inform the development and implementation of multifaceted innovative mealtime assistance and staff training programs to promote resident eating performance while fostering person-centered individualized mealtime care practice.